Adolescent information behaviour in everyday life decision making - Alica Kolarić; Colleen Cool; Ivanka Stričević (Vjesnik Bibliotekara Hrvatske)
Purpose. Within the field of information science, adolescent information behaviour as a part of the general decision making process is a relatively under-examined area. The way adolescents interact with information when making decisions influences decision outcomes and consequently affects their lives. Therefore, the study of information behaviour in the decision making process is an important area for research development. The goal of this paper is to take a step to advance research in this direction by reviewing what has been learnt and offering directions for future work.